The impact of Covid-19 on students’ mental health - Uddin, Miraz; Uddin, Burhan (Goodwood Publishing, 2021)
Purpose: The research has been conducted to investigate the influential factors on students’ mental health during the Covid-19. Research methodology: The research is quantitative in nature. The structured questionnaire has been prepared to collect the data from 250 Bangladeshi students through a personal interview method using a 7-point Likert scale. The research used the convenience sampling method to collect the data and data were analyzed through SPSS 25.0 software. Results: The research found that economic factors, social factors, and educational factors have a significant impact on the students’ mental health during the Covid-19 pandemic situation. Limitations: The study is limited by geographical and sample size in the aspect of students’ mental health during the pandemic situation. Contribution: All sorts of people will be benefited from this study obtaining a clear understanding and scenario about the students’ mental health during the pandemic situation. Educational institutions, teachers, psychologists, behavioral therapists, social researchers, politicians, legal agencies, and others that are engaged in the education sector will be fruitful by this study’s outputs. Governments and governmental agencies may plan and promote their strategies and policies by having a clear concept about students’ mental health during the Covid-19 pandemic. Keywords: Mental health, Student, Covid-19, Education, Social aspect, Economic condition